Transformasi Pola Komunikasi Sosial Dakwah Era New Media (Tantangan dan Peluang Bagi Persatuan Mubaligh Kabupaten Lingga) - Ahmad Hamdan; Romi Aqmal; Syafi'i Ali (Jurnal Ilmu Sosial dan Ilmu Politik, 2026)
The phenomenon of digital Islamic preaching (dakwah) has sparked new and compelling discourse in religious, media, and cultural studies due to its profound socio-religious implications. The transformation of dakwah communication through short-form, massively distributed content not only risks spreading misinformation among communities but may also cultivate radicalism and intolerance when misinterpreted. This study examines the transformation of dakwah communication patterns in the new media era within the Lingga Regency Preachers Association (PMKL), analyzing both its challenges and opportunities. Using a qualitative phenomenological approach, data was collected through observation, interviews, focus group discussions (FGDs), and documentation, then analyzed through qualitative descriptive methods. Findings reveal three key transformations: (1) a shift from conventional one-way communication to instant, multidirectional dissemination; (2) the rise of fragmented and personalized content; and (3) evolving linguistic styles and preaching models. Challenges for PMKL in the new media landscape include: preachers' need for digital literacy, diverse opinions on social media, ethical communication standards, limited content creativity, and uneven internet access in certain areas. Conversely, new media offers opportunities such as global information reach, extensive data accessibility, online community building, inter-preacher collaboration, and improved efficiency in time, transportation, and accommodation management.